A research design of potential application of public screen in student vicinity - Fu, Y.; Lugmayr, Artur; Hao, Z. (2012)
Public digital screens are increasingly distributed in the urban cities. There are diverse technologies and services carried out for the interaction between users and the digital displays. Additionally, the desire and needs of applying interactive displays in students' village rather than constraint in the modern cities arises in recent years as well. Thus, we conduct a study of the potential application of public screens for students concerning technology, services, content type and merchandizing. We also investigate in the different desire of other shareholders such as shop owners and community developer in order to gain a leveraged overview of public displays in student vicinity.